Peran perempuan dalam berwirausaha menuju pengembangan industri ekonomi kreatif di Desa Wisata Menari Getasan Kabupaten Semarang - Saadati, Nila (Nur Science Institute, 2022)
This research identifies the role of women as entrepreneurs. This study uses qualitative research methods carried out by field research. The location of this research is in Tanon